Princapls' leadership attributes: a predictor to secondary schools effectiveness - Bagobiri, Garba; Asimiran, Soaib; Basri, Ramli (Global Institute for Research & Education, 2014)
The anticipation to certify the effectiveness of secondary schools education in most of the third world countries today is determine by the principals’ Leadership Attributes which could be quantified based on the leadership training acquire by most principals. This paper examines the influence of Principals’ Leadership Attributes as a predictor for Secondary School Effectiveness towards students’ academic achievement. The study using secondary schools information with discusses analysis of existing supportive literature on the subject matter for its theoretical foundation to explore the principals’ Leadership Attributes and its contribution to School Effectiveness. With the principals’ Leadership Attributeswhich is mostly needed among schools principal in this ever changing world to sustain the Secondary Schools improvement and effectiveness also determines the growth and development of anation. This paper revealed that, not much substantial packages are put in place to improve the Leadership Attributes of principals among secondary schools in Nigeria most especially in Niger State North Central part of the country.This paper concluded that, leadership training for school principals will assist in improving their Leadership Attributes to overcome the numerous challenges facing most school principals nowadays and thereby contributes immensely towards the effectiveness of secondary schools in Niger state.